Characterization of Expanded Polystyrene by Pyrolysis Process for Plastic Waste to Fuel - Ravindra Pathak, Serajul Haque (International Journal of Advanced Science and Technology, 2020)
Present work demonstrates pyrolysis heat treatment of Expanded Polystyrene (EPS) to obtain liquid and gaseous fuels. Energy characterization of extracted fuels with different composition is compared with technical ASTM standards. The experimental tests were carried out using a temperature range from 300 ° C to 450°C, with intervals of 50°C, that is, at 300°C, 350°C, 400°C and 450°C, for EPS. It is found that optimum operating temperatures is 450°C for the highest oil production Based on the chromatographic analysis, it is determined that the oil obtained from EPS pyrolysis cannot be used as fuel, due to its chemical components, which have solvent properties, therefore, it would damage an internal combustion engine.